Comportamiento productivo de pollos cuello desnudo en pastoreo, más balanceado con inclusión de harina de follaje de yuca (manihot esculenta crantz) - Martínez Delgado, Mario Paúl (2016)
In the Experimental Farm "La María", in the Bird Program, Faculty of Animal Sciences, Quevedo State Technical University (UTEQ), located at km 7 via Quevedo- El Empalme, Canton Mocache, this work was carried out: "Productive performance of bare-neck chickens in grazing, more balanced with cassava foliage meal (Manihot esculenta Crantz)". With a duration of twelve weeks. The productive parameters were: food consumption (g), weight gain (g), feed conversion, yield to the channel, and profitability of treatments. For the first experiment 18 birds (6 birds / replicate) were used. The treatments were: T1 = Control (balanced, without flour); T2 = Balanced plus 4% of hfy; T3 = Balanced plus 8% of hfy. A completely randomized design (DCA) was used. In the second experiment 108 birds, six replicates were used. The treatments were: T1 = Control (0% restriction); T2 = (25% restriction); T3 = (50% restriction). A randomized complete block design (DBCA) was used. The results of this work were submitted to an analysis of variance (ANDEVA). For the comparison of means between treatments the Tukey test was used (P <0.05). The treatment with the 4% inclusion of hfy. Presented the best apparent retention of nutrients. In the productive behavior, the diet factor of the Control treatment chickens (0% restriction), obtained the best answers in all the indicators. In the sex factor males showed better responses than females in all indicators. From the results obtained, it can be concluded that up to 4% of hfy can be included in the diets that were restricted up to 25% with results that were close to the control without affecting their productive behavior. However, the control reported higher profitability.